Evaluation and optimization of district energy network performance: Present and future. (April 2021) - Wang, Yang; Zhang, Shanhong; Chow, David; Kuckelkorn, Jens M.
Abstract: The building sector accounts for the largest portion of total final energy consumption in most countries, and is responsible for around one third of carbon emissions, which have been regarded as the cause for global warming and climate changes. District energy network, which can supply consumers with heating/cooling and electricity, is an effective and proven approach to enhance energy efficiency and reduce carbon emissions. Currently, the approach of integrated energy systems (including renewable energy) tends to be increasingly necessary and significant for the district energy network. This article presents a comprehensive review of energy performance of district energy networks, focusing on optimization and evaluation of district heating network combining with other relevant energy systems and renewable technologies. This review consists of the concept of district energy network, typical applications of district energy network, and significant literatures of energy performance of various energy networks based on theoretical modelling and analysis, physical experimental studies and numerical simulations. Furthermore, over 30 factors affecting energy performance have been substantially investigated and assessed. This review has demonstrated that main effects on energy network performance are significantly linked to configurations and capacities of system, climate conditions (locations and time), and the interaction between various factors. An optimal overall performance of district energy network would need to integrate several advanced energy systems, e.g. a balanced energy network. Highlights: First review on performance for district energy network considering heating/cooling, electricity & gas. Various advanced technologies for energy network investigated via simulation/measurement. Parametric sensitivity analysis including diverse effects of 30+ parameters on energy performance. Comparison and evaluation on performance of different technologies applied in energy network. A novel next-generation energy network using several cutting-edge technologies developed in London.